Puella magi Oriko magica. Vol. 2 (Yen Press, 2013)
"Oriko is determined to use any means available to her in order to prevent the destruction she has glimpsed in the future. Her companion, Kirika, has been useful in creating a distraction by murdering other Magical Girls, but Oriko recognizes that the time for diversionary tactics has passed-- she must target the source directly and eliminate the threat. Little does she realize that her quarry has a protector who is as passionate about keeping the girl alive as Oriko is about seeing her dead. What future ultimately awaits in the eye-opening conclusion of Oriko Magica?!" -- p. [4] of cover.